Blow-up Rate of Solutions for P-Laplacian Equation (Journal of Partial Differential Equations, 2008)
" In this note we consider the blow-up rate of solutions for p-Laplacian equation with nonlinear source, u_t=div(|\u2207u|^{p-2}\u2207u)+u^q, (x,t)\u2208R^N\u00d7(0,T), N \u2265 1. When q > p - 1, the blow-up rate of solutions is studied."
Keywords: p-Laplacian equations; nonlinear source; blow-up rate